Single nucleotide variations in the ANXA5 promoter regulated piglet weight in the Min pig - Han, Mingyang; Zhang, Yingkun; Zhang, Yu; Yao, Diwen; Sun, Shupin; Li, Xiaoji; Yang, Xiuqin; Di, Shengwei; Wang, Xibiao; Cai, Jiancheng; Chen, Liping; Dai, Lihe; et al. (Frontiers in Veterinary Science, 2025)
ANXA5 is a pleiotropic candidate gene, however its effect on piglet production trait remains unclear. In this study, a novel SNP: g.-519 A > G was identified in ANXA5 promoter. In Min pigs, association analysis showed the birth weight of AA animals at g.-674 C > A was higher than that of the AC or CC piglets (p < 0.05), while the heterozygous of g.-519 A > G had a higher weight than the homozygote at day 3, 7, 14, 21 after birth (p < 0.05). Porcine ANXA5 and NR4A1 existed in piglets’ gastrointestinal tract, and NR4A1 localized to the nucleus and cytoplasm which regulated the expression of ANXA5. Luciferase reporter analysis demonstrated that the deletion of predictive NR4A1 binding region decreased the luciferase activity of porcine ANXA5 promoter (p < 0.05), and the A allele of g.-519 A > G within this region had significantly higher luciferase activity than the G allele (p < 0.01). In conclusion, this research suggested that g.-519 A > G was a piglet weight variant that regulated the transcription of ANXA5 partially by NR4A1.